(untitled) (Bangladesh Journal of Neuroscience, 2017)
Cerebral venous sinus thrombosis is an uncommon but important cause of stroke, especially in young-aged woman. Clinical presentation is variable, usually in the form of focal neurological deficit, seizure, headache and other features of raised intracranial pressure, leading to misdiagnosis or delay in treatment. Here we report 4 cases of venous sinus thrombosis with variable presentation. Diagnosis is confirmed by neuroimaging including magnetic resonance imaging with magnetic resonance venography of brain. Treatment consists of anticoagulation along with supportive management. Bangladesh Journal of Neuroscience 2017; Vol. 33 (1): 30-33